Association of Vertebral Endplate Microstructure with Bone Strength in Men and Women - McKay, MeiLissa (Bone, 2019)
Epidemiological and biomechanical evidence indicates that the risk of vertebral fracture differs between men and women, and that vertebral fracture frequently involves failure of the endplate region. The goal of this study was to compare the bone microstructure of the endplate region—defined as the (bony) vertebral endplate and underlying subchondral trabecular bone— between sexes and to determine whether any such sex differences are associated with vertebral strength. The bone density (volume fraction, apparent density and tissue mineral density) of the superior-most 2 mm of the vertebra, and the bone density and trabecular architecture of the next 5 mm were quantified using micro-computed tomography in human T8 (12 female, 16 male) and L1 (13 female, 12 male) vertebrae. Average density of the vertebra (integral bone mineral density (BMD)) was determined by quantitative computed tomography and compressive strength by mechanical testing. Few differences were found between male and female vertebrae in the density of the endplate region; none were found in trabecular architecture. However, whereas endplate volume fraction was positively correlated with integral BMD in male vertebrae (r=0.654, p<0.001), no correlation was found in the female vertebrae (r=0.157, p=0.455). Accounting for the density of the endplate region improved predictions of vertebral strength (p<0.034) and eliminated sex-specificity in the strength prediction that was based on integral BMD alone. These results suggest that the density of the endplate region influences vertebral fracture and that non-invasive assessment of this region’s density can contribute to predictions of vertebral strength in men and women.